Comparative Efficacy of Autologous Stromal Vascular Fraction and Autologous Adipose-Derived Mesenchymal Stem Cells Combined With Hyaluronic Acid for the Treatment of Sheep Osteoarthritis. Issue 7 (July 2018) - Lv, Xiaoteng; He, Jiyin; Zhang, Xue; Luo, Xuan; He, Na; Sun, Zhongwei; Xia, Huitang; Liu, Victor; Zhang, Li; Lin, Xiangming; Lin, Liping; Yin, Huabin; et al.
The current study explored whether intra-articular (IA) injection of autologous adipose mesenchymal stem cells (ASCs) combined with hyaluronic acid (HA) achieved better therapeutic efficacy than autologous stromal vascular fraction (SVF) combined with HA to prevent osteoarthritis (OA) progression and determined how long autologous ASCs combined with HA must remain in the joint to observe efficacy. OA models were established by performing anterior cruciate ligament transection (ACLT) and medial meniscectomy (MM). Autologous SVF (1×10 7 mononuclear cells), autologous low-dose ASCs (1×10 7 ), and autologous high-dose ASCs (5×10 7 ) combined with HA, and HA alone, or saline alone were injected into the OA model animals at 12 and 15 weeks after surgery, respectively. Compared with SVF+HA treatment, low-dose ASC+HA treatment yielded better magnetic resonance imaging (MRI) scores and macroscopic results, while the cartilage thickness of the tibial plateau did not differ between low, high ASC+HA and SVF+HA treatments detected by micro-computed tomography (µCT). Immunohistochemistry revealed that high-dose ASC+HA treatment rescued hypertrophic chondrocytes expressing collagen X in the deep area of articular cartilage. Western blotting analysis indicated the high- and low-dose ASC+HA groups expressed more collagen X than did the SVF+HA group. Enzyme-linked immunosorbent assay showed treatment with both ASC+HA and SVF+HA resulted in differing anti-inflammatory and trophic effects. Moreover, superparamagnetic iron oxide particle (SPIO)-labeled autologous ASC signals were detected by MRI at 2 and 18 weeks post-injection and were found in the lateral meniscus at 2 weeks and in the marrow cavity of the femoral condyle at 18 weeks post-injection. Thus, IA injection of autologous ASC+HA may demonstrate better efficacy than autologous SVF+HA in blocking OA progression and promoting cartilage regeneration, and autologous ASCs (5×10 7 cells) combined with HA potentially survive for at least 18 weeks after IA injection.